Pengaruh Pembelajaran Berbasis Masalah dengan Penguatan Keterampilan Fleksibilitas terhadap Hasil Belajar Kognitif - Aprianto, Agung; Praherdhiono, Henry; Wedi, Agus (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2021)
This research proves the influence of Problem Based Learning by strengthening flexibility skills on cognitive learning outcomes in grade VII students. In study the students are taught to think flexibly in order to resolve the problem that is related to the energy life. The type of Research used is quasi-experimental. The data collection technique used is the test technique . The pretest is done to retrieve a students' initial ability data, while the posttest is conducted to test the effect of treatment . In This research, three statistical tests will be carried out namely, (1) normality test , (2) homogeneity test , (3) hypothesis test . The results of the hypothesis analysis obtained H1 were received because the significance value was 0.001 < 0.05, so it can be concluded that there is influence of Problem Based Learning (PBL) by strengthening flexibility skills in science subjects on the learning outcomes of cognitive learning.